From Individual Existence to Ecological Responsibility: Søren Kierkegaard’s Private Theology and Its Implementation in the Congregation of GMIBM Sion Tonom - Solang, Zefanya R; Mawikere, Marde Christian Stenly; Poluan, Agnes Relly (Peneliti.net, 2025)
This article explores the relevance of Søren Kierkegaard’s concept of private theology in addressing the ecological crisis within the congregation of GMIBM Sion Tonom. Employing a qualitative-descriptive approach and theological reflection, the study finds that a personal, existential spirituality has the capacity to foster authentic and contextually grounded ecological engagement. Notions such as the leap of faith and the teleological suspension of the ethical demonstrate that personal faith can transcend prevailing social norms in pursuit of divine obedience. Amidst the structural limitations of the institutional Church, private theology emerges as a participatory and transformative spiritual foundation, enabling the development of grassroots ecotheological movements. A faith lived intimately becomes a source of moral courage for acting towards the integrity of creation.